Evaluation Of Science Text Book For Third Primary Grade In The Light Of Criteria Of The International Content - Majeed Aziz, Iman; Abdullah Ismail, Muna (Opción, 2019)
The present research aims to evaluate the science textbook for the third grade of primary in the light of the international standards for the content of science books. The research sample and community consisted of the science textbook for the third grade of the fourth edition of 2017. The analysis form adopted a tool to achieve the research objective. The validity and reliability of the tool has been verified. The results of the research showed that the field of (scientific inquiry) ranked first in the inclusion of field standards in the content of the book compared with the criteria of other fields as the top ten indicators of the field of (scientific inquiry) with its two criteria (questioning and inquiry skills) obtained high rates in the light of the criteria set by the research. In the light of the process of content analysis, while the indicators of other field obtained rates lower than the first and field different proportions of the criteria includ- ed in it. The current research recommended that the training programs of science teachers should include the international criteria content for science books to help them teach science in the primary stage by including the content to be included in the criteria and in balanced proportions.